Designing, manufacturing and mechanical tests of lattice structures based on triply periodic minimal surface - D. V. Sorokin; E. V. Moskvichev (Космические аппараты и технологии, 2024)
In recent decades Triply Periodic Minimal Surfaces have attracted significant research interest in many fields, such as automotive, aerospace, chemical industry, medicine, biomaterials and others. Cellular structures obtained from such surfaces have broad capabilities in tuning physical and mechanical properties to create new materials and structural elements. In this work, the authors examine the main issues of modeling cellular structures such as Gyroid, Schwarz Primitive, I-WP (I-graph-wrapped package) and Schwarz Diamond. For two selected types of cellular structures, Gyroid and I-WP, the range of parameters affecting the relative density (volume fraction) of the material in a cubic unit cell was investigated. Based on the unit cell, geometric models of specimens with a periodically repeating structure were created for mechanical testing. The specimens were manufactured on a 3D printer and tested for compression until failure while recording load diagrams and displacements of specimens points. Experimental studies led to the conclusion that the mechanical properties of the specimens significantly depend on the relative density (volume fraction) of the unit cell. Controlling the relative density can be useful for achieving the required mechanical properties of designed materials and structural elements with unique properties.